(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article considers the problem of adaptation of Kazakh Onims and their variability in Russian speech as a long-term use of Kazakh Onims in Russian oral speech leads to the functioning of various variants. In this case there is a problem of norm that needs a different solution for proper names in contrast to appellative lexis. The problem of variability in Russian studies arose in connection with the development of normalized activity and the dynamics of the literary norm. Therefore, initially the issues of variability and standardization are studied in parallel to obtain reliable access to the practical activity on compiling dictionaries, reference books in which there was necessary information of recommendatory nature.